Penerapan 7 Kebiasaan Anak Indonesia Hebat (7 KAIH) dalam Membentuk Budaya Positif Siswa Kelas IV SDN Polehan 2 Malang - Shendi Hendrar Satriyo; Deasy Amy Trisnayanti; Puspa Dewi Setyawati (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the implementation and effectiveness of the 7 Kebiasaan Anak Indonesia Hebat (7 KAIH) program in shaping a positive school culture among fourth-grade students at SDN Polehan 2 Malang. A descriptive qualitative approach with a case study design was employed to explore the character habituation process within the authentic school context. Participants included 32 students, two homeroom teachers, and one principal selected through purposive sampling. Data were collected using Likert-scale questionnaires, structured observations, semi-structured interviews, and documentation, with triangulation to ensure credibility. Data were analyzed using descriptive statistics (means and percentages) and thematic analysis. The findings show that the implementation of 7 KAIH reached an effectiveness level of 81.4%, categorized as highly effective. Social engagement and religious habits achieved the highest scores, while learning enthusiasm showed the lowest (73%). The lower achievement in learning enthusiasm was influenced by limited intrinsic motivation, excessive gadget use, and insufficient parental academic support, indicating that cognitive-related habits require stronger integration with active classroom learning strategies. Triangulation results revealed an 88% convergence level, confirming data consistency. The program effectively fostered discipline, tolerance, and mutual cooperation. Supporting factors included teacher role modeling and a conducive school environment, whereas family economic conditions and digital distractions were major constraints. The 7 KAIH model is recommended as a replicable best practice to strengthen character education in elementary schools.